ANALISIS KEMAMPUAN METAKOGNISI SISWA DALAM MENYELESAIKAN PERMASALAHAN MATEMATIKA DITINJAU BERDASARKAN GENDER - Nihayatul Hasybi; Dadang Rahman Munandar (SIGMA, 2021)
This study aims to describe students' metacognitive abilities in solving math problems in terms of gender. The type of research used in this research is qualitative with a descriptive exploratory approach. The subjects of this study were two students of grade 7 SMP Negeri 2 Sukatani. The instruments used were tests and interviews. With the data analysis technique using 4 flow, namely: 1) data collection, 2) data reduction, 3) presentation of data, and 4) drawing conclusions. The indikators used are three elements, namely planning, monitoring, and assessment (evaluation). The results of this study indicate that male students are not good enough to apply metacognition skills in solving math problems, because male students have not met the three indikators, only reaching 1 indikator, namely at the planning stage. Meanwhile, female students have implemented metacognition skills well, because they have fulfilled three indikators, namely planning, monitoring, and evaluation